New Media and Public Relations - KIM, Soojin (Institutional Knowledge at Singapore Management University, 2014)
The book provides theoretical reviews and application studies of the use of social media in public relations. This book helps readers explore conceptualization, impacts, and implications of social media for public relations theory and practices in a variety of contexts including corporate communication, political communication, not-for-profit and philanthropic organizations, health communication, and crisis communication. Chapters contain new theoretical concepts including W. Timothy Coombs’ "Internet Contagion Theory" and Jeong-Nam Kim’s "Cybercoping" as well as recent case studies of social media communication such as Japan’s 2011 Earthquake and BP oil spill crisis.